Influence of priming duration on the performance of Amaranths (Amaranthus cruentus L.) in Sokoto semiarid zone of Nigeria - Musa, Mukhtar; Singh, Ajit; Lawal, Aminu Aliyu (Hindawi Publishing Corporation, 2014)
Two field trials were conducted during the 2012 cropping season at the Fruits and Vegetable Teaching and Research Farm of the Department of Crop Science, Usman Danfodiyo University, Sokoto (located on latitude N-N and longitude -), to evaluate the effect of priming duration on the growth and yield of amaranth. Treatments consisted of four priming durations (2, 4, 6, and 8 hours) and control (where no priming was applied). The treatments were laid out in a completely randomized design (CRD) replicated three times for the germination test and randomized complete block design (RCBD) for the field trial. Data were collected on days to 50% germination, percentage germination, days to 50% emergence, and percentage emergence. Results revealed significant effect of priming duration on days to 50% germination, percentage germination, and days to 50% emergence. Soaking seeds for 2 hours reduced the number of days to 50% germination and emergence and also recorded higher germination. Thus, from the findings of this study, it could be concluded that priming amaranth seeds for 2 hours could be applied to enhance amaranth production.